CHANGE IN PHYSICAL PROPERTIES OF BANANA FRUITS DURING RIPENING STAGE - Tarek FOUDA; Adel Hamed EL-BAHNASAWY; Nourhan KASSAB (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of this study is measuring the physical properties of banana fruits. In this study we used Dessert bananas (Musa sap.) from local dedicated banana ripening rooms in the city of Santa, Gharbia Governorate in January 2024 was selected for experimental work. Banana ripening starts with a full green fruit, then pale green, then green yellow, then yellow with green tips, then bright yellow, then pale yellow and yellow with brown spots at last. The measurements indicators are physical properties such as length (L), width (W), thickness (T) arithmetic mean diameter (Da), mm, geometric mean diameter (Dg) mm, surface area (As) mm2, volume (V) mm3, and sphericity (φ) % of banana fruits. The results recorded that there was a rise in length of 140.97 mm to 151.01 mm, width of 34.06 mm to 38.83 mm, and thickness of 30.67 mm to 35.77 mm, in that order. For the Size and shape index indicators of banana fruits, the results showed that the projected area and shape index increased from 1914.5 to 2259.42 mm2 and from 3.83 to 4.5, respectively. Also, Elongation and Flakiness for banana fruits increased from 3.64 to 4.39 % and from 0.83 to 0.98 % respectively.